FLOOD HISTORY ANALYSIS AND ITS CONTRIBUTION TO FLOOD HAZARD ASSESSMENT. THE CASE OF MARATHONAS, GREECE - Diakakis, M. (Bulletin of the Geological Society of Greece, 2010)
Flood history analysis contributes decisively to a more realistic assessment of flood hazard. In this work, systematic data collection on past flood events in Marathonas area (Attica, Greece) together with the development of a database, allowed the thorough study of flooding phenomena and their evolution over time. The study area consists of three dominant catchments with rich flooding history, namely Rapentosa, Charadros and Kato Souli. Information gathered from governmental and insurance organizations, emergency agencies, the press, field interviews and other documentary sources, along with geomorphologic and geologic evidence, were stored, structured and analyzed in a GIS platform and were used to reconstruct flood events with detail. Valuable results were produced concerning the causes, the characteristics, the spatial distribution of damages and the extent of inundation for each event. Moreover, the rate of recurrence of flooding phenomena was calculated across the floodplain, so that the areas of higher risk were identified and delineated. The active part of the floodplain was outlined and its migration overtime was studied. Furthermore, the methodology underlined the imperfections of the existing risk mitigation strategy and the past emergency experiences were appraised in a way that they highlight the priorities and will help improve management of future situations of risk.